Magnetoelectric Effect in Two-Layer Composites with a Graded Magnetic Phase - Shut, V. N.; Trublovsky, V. L.; Laletin, V. M.; Yadroitsev, I. (Physics of the Solid State, 2020, Vol. 62, No. 11, pp. 2063–2069., 2020)
Samples of a homogeneous (x = 0, 0.1, and 0.2) and multilayer ceramics with a gradient composition (x = 0.2 → 0.1 → 0 → 0.1 → 0.2) based on solid solutions of (Ni1 − xZnx)Fe2O4 nickel–zinc ferrites have been manufactured using the thick-film technology. After sintering in a two-step mode, the gradient samples exhibited a smooth non-uniform distribution of chemical elements (Zn, Ni) over the thickness. The longitudinal (αE33) and transverse (αE31) magnetoelectric effects in two-layer PZT–nickel ferrite composites have been studied. In the absence of an external magnetostatic field, the values of magnetoelectric coefficients were negligible. The maximum value of the longitudinal magnetoelectric coefficient for composites with the gradient magnetic phase was practically two times higher than value of αE33 for homogeneous structures.
Article
Keywords: Nickel–zinc ferrites; Graded ceramics; Magnetic properties; Magnetoelectric effect